Hematological Adaptations to Post-Exercise Sauna Bathing With No Fluid Intake: A Randomized Cross-Over Study. Issue 4 (2nd October 2022) - Sitkowski, Dariusz; Cisoń, Tomasz; Szygula, Zbigniew; Surała, Olga; Starczewski, Michał; Sadowska, Dorota; Malczewska-Lenczowska, Jadwiga
ABSTRACT: Purpose : Sauna bathing is recommended to improve the sports training process, yet empirical evidence confirming its effectiveness is still inconclusive. We examined the effects of post-exercise sauna bathing on hematological adaptations and exercise capacity in healthy men. Methods : Thirteen physical education students participated in randomized cross-over study: two, 4-week interventions, with 10-week washout. The interventions involved 3 times per week 60-min stationary cycling either with 30-min of post-exercise sauna bathing (89 ± 3°C, 10 ± 2% RH) or without; no fluid was ingested during both exercise and sauna sessions. Before and after both interventions, participants were tested for total hemoglobin mass (tHb-mass), intravascular volumes, erythropoietin, ferritin, red blood cell parameters with reticulocyte fractions, along with maximal/peak and submaximal variables in a graded exercise test (GXT). Results : Regardless of intervention type, tHb-mass increased ( p = .014) whereas ferritin concentration decreased ( p = .027); however, changes in tHb-mass were within the range of typical error (<1.8%). Absolute and relative values of maximal power and power at gas exchange threshold, as well as peak oxygen uptake (all p < .010), also increased irrespective of intervention type. Conclusions : The use of post-exercise sauna bathing with fluid intake restrictions does not provide any additional benefits in tested variables over endurance training alone. Thus, further evidence is required before recommendations to utilize this post-exercise conditioning strategy are deemed valid.